Effect of Temperature Variation of Static Thermal Tensioning on Angular Distortion and Sensitization behavior of GMAW Welded SUS 304 Stainless Steel Plate - R.N. Akhsanu Takwim; Purwoko; Bayu Pranoto (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Due to its rust resistance properties, the use of stainless steels, especially SUS304 for industrial equipment is increasing. The manufacturing process that is often used is GMAW welding. One of the disadvantages of SUS304 is the occurrence of distortion and sensitization when welded. In this study, the effect of temperature variations of Static Thermal Tensioning on angle distortion and microstructure behavior due to GMAW welding of SUS 304 T-joint plates was studied. Heating by electric heater is given to both parts of the base metal plate SUS 304 5mm thick with temperature variations of 200 oC, 250 oC and 300 oC. Cooling water with a temperature of 24 oC is provided on the back side of the welded track. Welding using filler ER 304 with a diameter of 0.8 mm with welding parameters such as welding current, voltage, gas flow and travel speed controlled at 75 A, 22 V, 10 l/min and 8 mm/s, respectively. Angular distortion of welding results for each treatment temperature variation was measured using a bevel protractor, and perform metallographic test to knowing the microstructural behavior. The results of the measurement of the average angular distortion of three repetitions show that at a temperature of 250 C static thermal tensioning produces the smallest angular distortion of 3ᵒ70', compared to other temperature variations which produce angular distortion 4o45’ at 200 oC and 3o86' at temperature 300 oC. The findings of the largest Cr (carbide) deposits due to sensitization were found at a temperature of 300 oC at 16,49% and the lowest at a temperature of 200 oC at 7,05%